Lotka's Law and the Distribution of Authorship:A Case Study of Literature on RFID - Gayathri Devi, S. (Journal of Information and Knowledge, 2016)
The paper examines the distribution of authorship of papers on RFID to examine the validity of Lotka's Law. Papers from Web of Science on Radio Frequency Identification (RFID) for the years 1990 to 2010 were collected for the study. Lotka's Law is applied in its generic form, by using the least square technique, linear equation and finding the value of the constants and testing the same through Kolmogorov Smirnov Test and finding the Correlation Co-efficient. The values of exponent n and constant C obtained proved that Lotka's Law does not hold good for authorship distribution pattern in (RFID) research.